2018
DOI: 10.1080/07060661.2017.1415977
|View full text |Cite
|
Sign up to set email alerts
|

A blight disease on highbush blueberry associated withMacrophomina phaseolinain Serbia

Abstract: Unusual blight-like symptoms appeared on highbush blueberry plants in Serbia during August 2015 and infected plants showed browning and reddening of leaves, drying of foliage, and brown discoloration of internal vascular stem tissues. The objective of this study was to isolate and confirm a causal agent of the disease. Five diseased blueberry plants (2-yr-old), with visible brown discoloration in the wood, were collected for isolation on potato dextrose agar (PDA). Morphological analysis of the selected fungal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…O’Neal) indicated that inoculation of Macrophominavaccinii were pathogenic on blueberry stems which causes the stem turn brown with necrotic lesions. Similar symptoms caused by M.phaseolina have been reported on blueberry in Serbia, resulting in foliage death, and brown discoloration of internal vascular tissues at the basal part of the bush (Popović et al 2018). The brown lesion caused by M.vaccinii and M.phaseolina on blueberries differs from the widely reported charcoal rot diseases caused by Macrophominaphaseolina and M.pseudophaseolina (Su et al 2001, Salik 2007, Yang et al 2005, Zhang et al 2011, Sarr et al 2014, Sun et al 2015).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…O’Neal) indicated that inoculation of Macrophominavaccinii were pathogenic on blueberry stems which causes the stem turn brown with necrotic lesions. Similar symptoms caused by M.phaseolina have been reported on blueberry in Serbia, resulting in foliage death, and brown discoloration of internal vascular tissues at the basal part of the bush (Popović et al 2018). The brown lesion caused by M.vaccinii and M.phaseolina on blueberries differs from the widely reported charcoal rot diseases caused by Macrophominaphaseolina and M.pseudophaseolina (Su et al 2001, Salik 2007, Yang et al 2005, Zhang et al 2011, Sarr et al 2014, Sun et al 2015).…”
Section: Discussionsupporting
confidence: 63%
“…Blueberries ( Vaccinium spp.) are popular fruits because of their health benefits health, such as enhancing brain memory and preventing heart disease (Shi and Liu 2009, Popović et al 2018). Blueberries have been commercially cultivated worldwide, particularly in the USA, Canada and a few European countries (Evans and Ballen 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These fungi are known as endophytes, latent pathogens, pathogens and saprophytes and they usually cause disease when their hosts are under stress [9]. In Serbia, Botryosphaeriales are important pathogens of woody and vascular plants causing die-back, cankers, leaf blights, shot hole disease, fruit and root rot [13][14][15][16][17][18]. The pathogenicity of Botryosphaeriales is of a particular importance in urban environments as city parks are mostly comprised of plants belonging to diverse taxonomic groups and these fungi can infect multiple hosts [19].…”
Section: Introductionmentioning
confidence: 99%